The Emergence of Chromosomally Located blaCTX-M-55 in Salmonella From Foodborne Animals in China - Zhang, Chuan-Zhen; Ding, Xiao-Min; Lin, Xiao-Ling; Sun, Ruan-Yang; Lu, Yue-Wei; Cai, Run-Mao; Webber, Mark A.; Ding, Huan-Zhong; Jiang, Hong-Xia (Frontiers in Microbiology, 2019)
The emergence and increase in prevalence of resistance to cephalosporins amongst isolates of Salmonella from food animals imposes a public health threat. The aim of the present study was to investigate the prevalence and characteristics of CTX-M-producing Salmonella isolates from raw meat and food animals. 27 of 152 (17.76%) Salmonella isolates were ESBL-positive including 21/70 (30%) from food animals and 6/82 (7.32%) from raw meat. CTX-M-55 was the most prevalent ESBL type observed (12/27, 44.44%). 7 of 12 CTX-M-55-positive Salmonella isolates were Salmonella Indiana, 2 were Salmonella Typhimurium, 2 were Salmonella Chester, and the remaining isolate was not typeable. Eight CTX-M-55-positive Salmonella isolates were highly resistant to fluoroquinolones (MICCIP=64ug/mL) and co-harbored aac(6’)-Ib-cr and oqxAB. Most of the CTX-M-55 positive isolates (11/12) carried blaCTX-M-55 genes on the chromosome, with the remaining isolate carrying this gene on a transferable 280kb IncHI2 plasmid. A chromosomal blaCTX-M-55 gene from one isolate transferred onto a 250kb IncHI2 plasmid which was subsequently conjugated into recipient strain J53. PFGE and MLST profiles showed a wide range of strain types were carrying blaCTX-M-55. Our study demonstrates the emergence and prevalence of foodborne Salmonella harboring a chromosomally-located blaCTX-M-55 in China. The co-existence of PMQR genes with blaCTX-M-55 in Salmonella isolates suggests co-selection and dissemination of resistance to both fluoroquinolones and cephalosporins in Salmonella via the food chain in China represents a public health concern.